Molecular cloning of a steroid-regulated 108K heat shock protein gene from hen oviduct. - Kleinsek, D A (1986)
The natural gene for a steroid inducible 108K heat shock protein has been isolated from a lambda genomic library prepared from hen oviduct tissue. Genomic DNA blots indicate that it exists as a single copy gene in the chick oviduct haploid genome. The 9.9 kilobase gene codes for a messenger RNA of 2733bp (21) and is split into 18 exons as established by sequence comparison of cDNA and genomic clones. The 3' end of the gene contains a repetitive element which shares homology with the CR1 family of repeats. The first exon contains both the untranslated leader and coding regions of the gene. The promoter region is rich in G + C residues (70%) and the dinucleotide CG. This 5' flanking segment contains bases similar both in sequence and location to the Goldberg-Hogness TATA homology and consensus sequence CCAAT. A consensus sequence located upstream of steroid hormone responsive chicken genes is found at -267 and on a reverse orientation at -593. The structure of this gene is of interest since the presence of introns in heat shock genes is rare in any species examined to date. Furthermore, this gene lacks the previously described heat shock promoter consensus sequence (C-GAA-TTC-G) present in other species.